Rugoscopy In Five Different Ethnic Groups Of Pakistani Population - Sara Gardezi; Nuzhat Hassan; Sarwat Memon; Arsalan Mughal (ziauddin University, 2022)
Background: Rugoscopy is the study of palatal rugae. Palatal rugae are irregular ridges on the mucosal membrane projections extending from incisive papilla to anterior part of palate. They are unique to an individual similar to finger prints. They support in post mortem identification. The aim of this study was to find out predominant rugae patterns and their variations amongst five different linguistic populations of Pakistan. Methods: A Cross sectional comparative study was conducted at different campuses of Out Patient Departments of Ziauddin Hospital and Al-Zohra Welfare Association, Karachi from July 2016 to January 2017. The study population of 456 subjects included five Pakistani races namely Balochi, Punjabi, Pushto, Sindhi and Urdu speaking with age groups between 15 to 55 years. The shapes of rugae were evaluated on dental casts using the Kapali et al's classification. Chi square test was used for association of qualitative variables. A p-value of ≤ 0.05 was considered significant. Results: There was a significant difference in rugae pattern amongst five ethnicities of Pakistan (p= 0.010). The most prevalent rugae shape among Punjabi and Pushto was wavy followed by straight and curved patterns. Among Sindhi and Urdu speaking the most common pattern was wavy followed by curved and straight rugae pattern. Balochi speaking presented with curved, wavy and divergent patterns. The least common among all the races was circular rugae pattern. Conclusion: This study indicates an association between rugae pattern and ethnic groups. This can be used as an additional tool in forensic identification.